Self-reported oral health problems and the ability to organize dental care of community-dwelling elderly aged ≥75 years - M. H. Bakker; A. Vissink; S. L. W. Spoorenberg; K. Wynia; A. Visser (BMC, 2020)
Abstract Background It is unclear how many community-dwelling elderly (≥75 years) experience oral health problems (e.g. pain, dry mouth, chewing problems) and how they manage their dental care needs. This study aimed to assess self-reported oral health problems in elderly who are frail or have complex care needs, and their ability to organize dental care when reporting oral pain. Methods Three thousand five hundred thirty-three community-dwelling elderly participating in the "Embrace" project were asked to complete questionnaires regarding oral status and oral health problems. Frailty was assessed with the Groningen Frailty Indicator (GFI). Intermed for Elderly Self-Assessment (IM-E-SA) was used to determine complexity of care needs. Next, elderly who reported oral pain were interviewed about their oral pain complaints, their need for dental care, and their ability to organize and receive dental care. For statistical analyses Chi2-tests and the one-way ANOVA were used. Results One thousand six hundred twenty-two elderly (45.9%) completed the questionnaires. Dry mouth (11.7%) and oral pain (6.2%) were most frequently reported. Among the elderly reporting oral pain, most were registered at a local dentist and could go there when needed (84.3%). Robust elderly visited the dentist independently (87%), frail (55.6%) and complex (26.9%) elderly more often required assistance from caregivers. Conclusions Dry mouth and oral pain are most reported oral health problems among community-dwelling elderly. Elderly with complex care needs report most oral health problems. In case an elderly seeks dental treatment to alleviate an oral pain complaint, most elderly in this study were able to organize dental care and transport to the dentist. Frail and complex elderly often need assistance from caregivers to visit the dentist. Therefore caretakers should keep in mind that when frailty progresses, visiting a dentist may become more and more difficult and the risk for poor oral health increases.